PENINGKATAN KETERAMPILAN BERPIKIR KRITIS DAN SIKAP KEMANDIRIAN BELAJAR MENGGUNAKAN MODEL PROBLEM BASED LEARNING PADA TEMA 7 DI KELAS V MIM 01 SAMBONG - Rois Triwibowo; Badarudin Badarudin; Aji Heru Muslim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2020)
This study aims to improve critical thinking skills and independent learning of students through problem based learning models in class V. The method used in this research is classroom action research. PTK is carried out for 2 cycles, each cycle consisting of 2 learning meetings with 1 meeting one learning implementation plan. The research procedure consists of several stages, namely the planning, action, observation and reflection. The research subjects were class V MIM 01 Sambong with 22 students consisting of 8 male students and 14 female students. This research data collection tool uses a critical thinking skills test, learning independence attitude questionnaire, student activity observation sheet and teacher activity observation sheet. The results of increasing critical thinking skills and students' learning independence can be seen at each stage of the cycle. The results of this CAR show that PBL models can improve critical thinking skills and learning independence in class V MIM 01 Sambong. Students show each cycle. Cycle 1 gets an average of 3.04 while cycle 2 gets an average of 3.74 with good criteria meanwhile in independent learning, cycle 1 gets average of 3,2 in the other hand cycle 2 gets average of 3,67 with good criteria